(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Computational fluid dynamics (CFD) has been used by numerous researchers for the simulation of flows around wind turbines. Since the 2000s, the experiments of NREL phase VI blades for blind comparison have been a de-facto standard for numerical software on the prediction of full scale horizontal axis wind turbines (HAWT) performance. However, the characteristics of vortex structures in the wake, whether for modeling the wake or for understanding the aerodynamic mechanisms inside, are still not thoroughly investigated. In the present study, the flow around NREL phase VI blades was numerically simulated, and the results of the wake field were compared with the experimental ones of a one-to-eight scaled model in a low-speed wind tunnel. A good agreement between simulation and experimental results was achieved for the evaluation of overall performances. The simulation captured the complete formation procedure of tip vortex structure from the blade. Quantitative analysis showed the streamwise translation movement of vortex cores. Both the initial formation and the damping of vorticity in near wake field were predicted. These numerical results showed good agreements with the measurements. Moreover, wind tunnel wall effects were also investigated on these vortex structures, and it revealed further radial expansion of the helical vortical structures in comparison with the free-stream case.